Micro-scale wind resource assessment in complex terrain based on CFD coupled measurement from multiple masts. (15th March 2019) - Tang, Xiao-Yu; Zhao, Shumian; Fan, Bo; Peinke, Joachim; Stoevesandt, Bernhard
Highlights: A validated methodology for micro-scale wind resource assessment in complex terrain. Advanced computational fluid dynamics are coupled with on-site measurements. The dynamic velocity estimations at any point within the wind field are obtained. A weight refinement scheme is designed to merge the estimations from multiple masts. Abstract: To date, the micro-scale wind resource assessment for complex terrain has always been a challenging mission, due to the flow field complexity caused by the local topography. In this paper, a novel method, combining on-site measurement from multiple masts and computational fluid dynamics (CFD) simulations, is proposed for complex terrain site assessment. It is designed to accomplish the spatial variability reproduction of wind energy distribution, as well as the dynamic wind velocity estimation of any desired positions within the concerned region. CFD simulations are carried out to provide detailed wind fields, which implicitly carry the correlations of physical properties with the concerned space. The on-site measurement data from multiple masts are integrated into the assessment process, to provide dynamical corrections based on the reference solutions obtained from the CFD simulations. A high-resolutional wind resource distribution and accurate wind velocity estimations are achieved. A detailed case study on micro-scale wind resource assessment for a wind farm with complex terrain, located in China is presented for validation.